2021
DOI: 10.3126/jpan.v10i2.48999
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of Children in Home Confinement in Nepal During Covid-19 Pandemic

Abstract: INTRODUCTION Since the declaration of COVID-19 as a pandemic there has been many public health strategies implemented to decrease it's extraordinarily adverse consequences. On March 18 2020, an estimated 107 countries around the world implemented national school closures and the Government of Nepal followed sooth on March 19. Children across European countries felt isolated due to the lockdown according to Save the Children, with increasing levels of feeling psychological distress. The effects of COVID-19 may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Orchid comprises various attractive flowers, they not only add beauty but also have many medicinal benefits. In Nepal, Rajbhandari et al, (2014) reported 107 genera and 451 species of orchids. Orchids are perennial herbs.…”
mentioning
confidence: 99%
“…Orchid comprises various attractive flowers, they not only add beauty but also have many medicinal benefits. In Nepal, Rajbhandari et al, (2014) reported 107 genera and 451 species of orchids. Orchids are perennial herbs.…”
mentioning
confidence: 99%